ANALISIS DAMPAK PEMBIAYAAN DANA BERGULIR KUR (KREDIT USAHA RAKYAT) TERHADAP KINERJA UMKM (Studi Kasus di Daerah Istimewa Yogyakarta) - V. Wiratna Sujarweni; Lila Retnani Utami (Jurnal Bisnis dan Ekonomi, 2015)
This study aims to find out how much the role of the People's Business Credit (KUR) meningkatakna performance in small and medium enterprises (SMEs) in Yogyakarta. To determine the difference in performance (the cost of production, turnover, profit, and working hours) MSME fund before and after the People's Business Credit (KUR). The research population is the population of this study is the Small and Medium Enterprises in the province who get help KUR, methods of sample with purposive sampling using criteria as follows: SMEs in Sleman and Bantul, which get KUR funds in 2013 and 2014, then the second technique with insedental sampling and sample that can be affordable to be sampled. Using the technique of collecting secondary data, the identity of respondents, the data cost of production, turnover and profit as well as the monthly working hours. The analysis tool used is descriptive testing and test the difference paired sample t-test. The results that the People's Business Credit (KUR) was instrumental in meningkatakna performance in small and medium enterprises (SMEs) in Yogyakarta, evidenced from the findings that the cost of production, turnover, profit, and working hours are increased before and after getting KUR funds.Keyword: people's business credit (kur), small and medium enterprises (smes), costs of production, turnover, profit, working hours